The art of the storyteller: «Mystical» and «rational» aspects - S. Yu. Nekliudov; Bamao Daiji (Шаги)
An epic storyteller is an individual who has devoted his life to performing heroic-epic tales in front of fellow villagers or other audiences. There are many stories about how a prospective storyteller acquires his creative abilities. This acquisition basically comes in two varieties. The first type is a «mythological» one. A person receives his poetic gift in a mystical way, either voluntarily or by supernatural compulsion, which can be called «storyteller’s initiation» (by analogy with shamanic initiation). As a rule, it happens when the future narrator is a child or an adolescent, and it happens without witnesses (the boy / young man is looking after cattle, after a strong thunderstorm, in a dream, etc.). The «patron of initiation» is almost always a representative of another world, often the spirit of the hero who is celebrated in the epic. The process of acquiring the «gift» usually coincides with mystical reception of the texts themselves in their verbal and musical form. Any attempt to refuse the «gift» brings misfortune and illness. The second type is a «realistic» one. A person is interested in songs and tales from childhood, memorizes them and tries to repeat them. Having gained approval, he becomes an apprentice to a renowned storyteller (singer, musician), observes the master’s work, adopts his skills and techniques, memorizes the repertoire, learns to control his voice and handle an instrument. In addition to practical significance, «apprenticeship» can have a symbolic function. Often, only the passage through such a «school» gives a novice storyteller the right to perform in front of an audience, for which he is blessed by his mentor, who also acts as a «patron of initiation». If the otherworldly character performs an «introductory» initiation, endowing the storyteller with the gift of poetry, the mentor completes the «initiation» by granting permission to perform (sometimes it can be done by another authoritative person). Thus, there are direct correspondences between these two types, there is a certain common model based on the first (i. e. «mythological») type of «storyteller’s initiation».